Penerapan Pendekatan Kontekstual melalui Model Pembelajaran Investigasi Kelompok untuk Meningkatkan Keterampilan Sosial Siswa Kelas X-3 SMA Negeri 1 Boyolali Tahun Pelajaran 2012/2013 - Chandra Adi Prabowo; Puguh Karyanto; Baskoro Adi Prayitno; Ristanti Yustin (BIO-PEDAGOGI, 2013)
The purpose of the research to improve the social skill of the X-3 graders of SMA Negeri 1 Boyolali in the school year of 2012/2013 by applying the contextual approach with group investigation learning model. Research method was a Classroom Action Research designed some cycles encompassing 4 stages: planning, acting, observing, and reflecting. The subject of research was the X-3 graders of SMA Negeri 1 Boyolali in the school year of 2012/2013. The data was obtained using non-test technique including interview and questionnaire. The data was analyzed using a descriptive qualitative technique as well as data validation using technique triangulation. Result of the research showed the improved achievement of student social skills. The conclusion was that the application of contextual approach using group investigation learning model could improve the social skill of the X-3 graders of SMA Negeri 1 Boyolali in the school year of 2012/2013. Key Words: Contextual Approach, Group Investigation, Social Skill